A complex model for the permeability and porosity of porous media. (23rd November 2017) - Tan, Xiao-Hua; Jiang, Li; Li, Xiao-Ping; Li, Yue-Yang; Zhang, Kai
Highlights: A complex model for the permeability and porosity of porous media is developed. The characters of pore microstructure and fluid in porous media are considered. This model reveals the all kinds of fluids flow in variety of porous media. The predictions of the model show good agreement with available experimental data. The proposed model can be used to characterize the flow in porous media. Abstract: Transport phenomenon in porous media is essential in various scientific and engineering fields. The permeability and porosity of porous media serve important functions in transport phenomena. In this study, a complex model that considers the characters of pore microstructure and fluid in porous media is developed for the permeability and porosity of porous media. The flow rate expressions of this model are compared with those of previous models. As the proposed models relate the properties of fluids to the structural parameters of porous media, the various expressions of the developed model can reveal the phenomena of all types of fluid flow in a variety of porous media. The predicted permeabilities and porosities show good agreement with the available experimental data and illustrate that the proposed model can be used to characterize flow in porous media.